ANALISIS PENGARUH LINGKUNGAN KERJA DAN KARAKTERISTIK INDIVIDU TERHADAP EFEKTIVITAS KERJA KARYAWAN PT. KENCANA INTI PERKASA MEDAN - Jane Lousie Endra; Imanuel Tarigan; Syawaluddin Syawaluddin (JURNAL BISNIS KOLEGA, 2019)
Abstract. This research was conducted at PT. Kencana Inti Perkasa Medan. PT. Kencana Inti Perkasa Medan which is a company engaged in oil palm management.The population and sample in this study were 42 employees. The sampling technique used is saturated samples Data collection techniques are pembainigain kueisoner, interviews and documentation studies. Data analysis uses validity and reliability test, classic assumption test, multiple linear regression analysis, determinant coefficient and hypothesis testing. Conclusion in the study that the Work Environment influences the Work Effectiveness of PT. Kencana Inti Perkasa Medan. Individual characteristics affect the Work Effectiveness of PT. Kencana Inti Perkasa Medan. Work Environment and Individual Characteristics affect the Work Effectiveness of PT. Kencana Inti Perkasa Medan. The magnitude of the coefficient of determination can be seen from the value of Adjusted R Square of 0.428, which means the work environment and individual characteristics can explain the work effectiveness of employees at 42.8% and the remaining 57.2% (100-42.8) influenced by other variables outside of this study like: analysis of position, education and so on.Â Keywords: Work Environment, Individual Characteristics, Work Effectiveness